Tuning of Luminescent and Magnetic Properties via Metal Doping of Zn-BTC Systems - Taoguang Qu; Qiang Wei; Carlos Ordonez; Jennifer Lindline; Michael Petronis; Marina S. Fonari; Tatiana Timofeeva (Crystals, 2018)
In order to assess how metal doping affects the luminescence and magnetic properties of anionic Metal-Organic Frameworks (MOFs), seven single-metal doped MOFs M-Zn-BTC{Me2NH2+} (M = Co, Cu, Ni, Mn, Ca, Mg, Cd) and three dual-metal doped MOFs Zn-M1-M2-BTC{Me2NH2+} (M1 = Co, Cu; M2 = Ni, Co) were synthesized. Trace amounts of different metals were doped via addition of another metal salt during the synthetic process. All compounds retained the same crystal structure as that of the parent Zn-BTC{Me2NH2+} MOF, which was supported by single crystal and powder X-ray diffraction studies. Thermal Gravimetric Analysis (TGA) of these compounds also revealed that all MOFs had similar stability up to ~450 °C. Solid state photoluminescent studies indicated that Zn-Mn-BTC{Me2NH2+}, Zn-Cd-BTC{Me2NH2+}, and Zn-Ca-BTC{Me2NH2+} had a significant red shifting effect compared to the original Zn-BTC{Me2NH2+} MOF. Applications of this doping method to other MOF systems can provide an efficient way to tune the luminescence of such systems, and to obtain a desired wavelength for several applications such as sensors and white light LED materials. Because Zn, Co, Cu, Ni, Mg have magnetic properties, the effect of the doping metal atom on the magnetism of the Zn-BTC{Me2NH2+} networks was also studied. To characterize the magnetic behavior of the synthesized MOFs, we conducted low-temperature (10 K) saturation remanence experiments in a 3 Tesla applied field, with the principal goal of identifying the domain state of the synthesized materials (Zn, Zn-Co, Zn-Cu-Co, Zn-Cu-Ni, Zn-Mg, Zn-Mn, Zn-Ni-Co, Zn-Ni). During room/low temperature saturation magnetization experiments, Zn, Zn-Co, Zn-Cu-Co, and Zn-Cu-Ni systems yielded data indicative of superparamagnetic behavior, yet during zero field and field cooled experiments Zn-Co showed a slight paramagnetic effect, Zn showed no temperature dependence on warming and Zn-Cu-Co and Zn-Cu-Ni demonstrated only a slight temperature dependence on warming. These behaviors are consistent with ferromagnetic ordering. Zero field and field cooled experiments indicate that Zn-Mg and Zn-Ni have a ferromagnetic ordering and Zn-Mn and Zn-Ni-Co show paramagnetic ordering behavior.